Digital Diversification and Product Development Strategy for Established Firm in Toll Road Industry Using Effort-Impact Matrix - Imaduddin, Muhammad (Riviera Publishing, 2025)
As an established firm in the toll road industry, JMTO faces challenge in sustaining growth and reducing risk from reliance on toll operation revenue as a cash cow. Jasa Marga through its subsidiary, PT Jasamarga Tollroad Operator (PT JMTO), perform digital business diversification leveraging its resources and capabilities in digital leadership. Several related diversification initiatives have been developed particularly in parking management, digital payment, and smartphone application development applying economic-of-scope. This research aims to formulate innovation management strategy in diversification and product development. A mixed method of qualitative and quantitative analysis is through semi-structured interviews with the chief commissioner, board of directors and middle management of JMTO, digital business client, and the collection of statistical data from Travoy and Let It Flo user, as well as number of clicks in Travoy app. Travoy app performance is evaluated based on ‘Importance’ measured by the number of clicks and ‘Performance’ measured by the number of feature reviews. The average number of normalized performance is 0,957, meanwhile normalized importance is 0,149. This indicates that most of Travoy features has good performance, but their low importance suggests that many are perceived by users as less essential despite their performance. According to interview with JMTO’s commissioner and management, the results indicate that JMTO’s competitive advantage is derived from its digital leadership, technology infrastructure and capabilities, as well as market positioning as Indonesian biggest toll road operator. Meanwhile, based on the interview with external key respondents, Customer Perceived Value can be categorized into Utilitarian Value, Monetary Value, and Reputation Value. The proposed strategy is formulated with TOWS matrix, then evaluated based on the effort and potential impact according to JMTO’s chief commissioner and top management, subsequently mapped with Effort-Impact Matrix. From 19 proposed strategies, 16 strategies are determined will have the potential impact and recommend for implementation.